Analysis of the Influence of Third Party Funds, Capital Adequacy, and Credit Distribution on Banking Profitability with Operational Efficiency as a Moderating Variable - Sabri; Muhammad Fahmi; Rudi Kurniawan; Sari Rusmita; Vitriyan Espa (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the effect of Third Party Funds (TPF), Capital Adequacy, and Credit Distribution on banking profitability, with Operational Efficiency as a moderating variable. This study uses a quantitative approach with secondary data from the financial statements of Regional Development Banks (BPD) during the period 2021–2023, namely the post-COVID-19 pandemic period. Data processing was carried out using the SPSS version 25 application. The results of the study showed that TPF did not have a significant effect on profitability, indicating that the amount of funds collected was not necessarily accompanied by the effectiveness of their utilization. On the other hand, Capital Adequacy and Credit Distribution were proven to have a significant effect on bank profitability. Operational Efficiency acts as a moderating variable that strengthens the relationship between Capital Adequacy and profitability, but is unable to moderate the effect of TPF or Credit Distribution. This finding supports the Signaling Theory, which states that capital adequacy and operational efficiency can be positive signals for bank performance, especially in the context of post-pandemic economic recovery.